2023
DOI: 10.3389/fcell.2023.1199519
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Kupffer cells in NAFLD and NASH: mechanisms and therapeutic interventions

Abstract: Non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) are emerging as the leading causes of liver disease worldwide. These conditions can lead to cirrhosis, liver cancer, liver failure, and other related ailments. At present, liver transplantation remains the sole treatment option for end-stage NASH, leading to a rapidly growing socioeconomic burden. Kupffer cells (KCs) are a dominant population of macrophages that reside in the liver, playing a crucial role in innate immunity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 161 publications
(153 reference statements)
0
10
0
Order By: Relevance
“…[35] The activation of Kupffer cells by liver lipid infiltration leads to the expression of various inflammatory factors and simultaneously contributes to the inflammatory cascade. [36] In addition, a previous study reported that nonalcoholic fatty liver disease aggravates AP by increasing bacterial translocation in the liver and pancreas. [37] This finding may explain the reason for the association between the severity of HTG-AP and PCT in the present study, which is a sensitive indicator of bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…[35] The activation of Kupffer cells by liver lipid infiltration leads to the expression of various inflammatory factors and simultaneously contributes to the inflammatory cascade. [36] In addition, a previous study reported that nonalcoholic fatty liver disease aggravates AP by increasing bacterial translocation in the liver and pancreas. [37] This finding may explain the reason for the association between the severity of HTG-AP and PCT in the present study, which is a sensitive indicator of bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, we showed that CIH increased levels of F4/80 staining, a macrophage cell marker, in both control and HF diet animals, confirming the increased inflammation in these conditions. Knowing that F4/80 staining is high in Kupfer cells and in liver monocyte-derived macrophages (MoMFs) [54,55] and that the activation of these cells drives macrophage polarization and activation [56,57], it is plausible to conclude that CIH drives liver inflammation, contributing to hepatic and whole-body metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In MASH, liver inflammation triggers the activation of KCs, as well as cells of the immune system that infiltrate the liver from the bloodstream, leading to fibrosis progression ( 104 ). KCs and monocyte-derived macrophages are indeed essential for the maintenance the immune function and serve as the first-line defense against pathogens.…”
Section: Gas6 and Tam Receptorsmentioning
confidence: 99%
“…In the context of liver inflammation, M1 macrophages contribute to hepatic steatosis, inflammatory cells recruitment and fibrosis activation, while M2 macrophages have anti-inflammatory and reparative functions. Thus, it has been demonstrated that M1/M2 ratio gradually increases during MASLD progression ( 104 , 105 ). After the development of hepatic steatosis, KCs secrete chemotactic substances facilitating the infiltration of monocytes.…”
Section: Gas6 and Tam Receptorsmentioning
confidence: 99%